Мои звери: [рассказы] / Владимир Дуров - Дуров Владимир Леонидович (Внеклассное чтение, 2011)
Экземпляры: М/а ДБ (20131119) / Инвентарный номер: 100332 / Цена: 66.50 / Авт.знак: Д 84 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6